Faktor Pengaruh Purchase Intention Berdasarkan Perspektif Konsumen pada Aplikasi Mobile Online Travel Booking - Noprisson, Handrie; Utami, Marissa; Marissa Utami (JSAI (Journal Scientific and Applied Informatics), 2020)
The development of the online travel booking business must be followed by increased revenue to maintain the trust of business partners such as investors and merchants. Increased purchases by consumers can be supported by several factors, one of which is purchase intention from a consumer perspective. This study looks at how the influence of a consumer perspective based on trust, perceived value, brand image, product diagnosicity on increasing purchase intention for online travel booking applications. Stages of research include data collection, data processing using SMARTPLS, interpretation of data processing results and drawing research conclusions. As a result of the study, the trust factor has the influence on purchase intentions with a t-value of 8.280. The perceived value influences purchase intentions in the online travel booking application with a t-value of 7.091. Brand image also has an influence on purchase intention with a score of 5.253.